Epidemiology and phylodynamics of multiple clades of H5N1 circulating in domestic duck farms in different production systems in Bangladesh - Islam, Ariful; Hossain, Mohammad Enayet; Amin, Emama; Islam, Shariful; Islam, Monjurul; Sayeed, Md Abu; Hasan, Md Mehedi; Miah, Mojnu; Hassan, Mohammad Mahmudul; Rahman, Mohammed Ziaur; Shirin, Tahmina (Frontiers in Public Health, 2023)
Waterfowl are considered natural reservoirs of the avian influenza viruses (AIV). However, the transmission and evolutionary patterns of AIV and its subtypes in duck farms are poorly documented in Bangladesh. Thus, we conducted a cross-sectional study in ducks from 9 districts between 2019 to 2021 to determine the prevalence of AIV and its subtypes H5 and H9, risk factors, and the phylodynamics of H5N1 clades circulating in domestic duck farms in Bangladesh. We tested the swab samples for the matrix gene (M gene), followed by H5, H7, and H9 subtypes using rRT-PCR. We then used exploratory analysis to determine AIV and subtype prevalence in different production systems and multivariable logistic regression to identify the factors that influence duck AIV and A/H5 prevalence. We conducted a Bayesian phylogenetic analysis to generate a time-scaled maximum clade credibility (MCC) tree of the H5N1 viruses . AIV prevalence for the overall sampled duck was 24.9% (95% CI: 21.3-28.9). AIV prevalence was highest in nomadic duck (39.8%; 95% CI: 32.9-47.1), followed by commercial (24.6%; 95% CI: 14.5-37.3), and backyard duck (14.4%; 95% CI: 10.5-19.2). The H5 prevalence was also highest in nomadic ducks (19.4%; 95% CI: 14.0-25.7) In contrast, the farm level AIV prevalence was 40.4%; backyard farms had a prevalence of 29.1%, commercial farms had a prevalence of 63.6%, and nomadic farms had a prevalence of 75.8%. We found ducks from nomadic farms (AOR: 2.4; 95% CI: 1.45-3.93) compared to backyard farms, juvenile ducks (AOR: 2.2; 95% CI: 1.37–3.61) compared to adult ducks, and sick ducks (AOR: 11.59; 95% CI: 4.82–32.44) compared to healthy ones have a higher risk of AIV. the two clades of H5N1 (2.3.2.1a and 2.3.4.4b). circulating among ducks in Bangladesh . The clade 2.3.2.1a reassorted in 2015, is silently evolving, and has at least formed nine subgroups. Additionally, a new clade 2.3.4.4b emerged in ducks in Bangladesh by the end of 2020 and clustering with viruses from Japan, China, and Africa indicates that migratory birds of the Central Asian flyway may influence the transmission of this novel clade in Bangladesh.